Thymic Self-Antigen Expression for the Design of a Negative/Tolerogenic Self-Vaccine against Type 1 Diabetes - Aziz Alami Chentoufi; Vincent Geenen (Clinical and Developmental Immunology)
Before being able to react against infectious non-self-antigens, the immune system has to be educated in the recognition and tolerance of neuroendocrine proteins, and this critical process essentially takes place in the thymus. The development of the autoimmune diabetogenic response results from a thymus dysfunction in programming central self-tolerance to pancreatic insulin-secreting islet β cells, leading to the breakdown of immune homeostasis with an enrichment of islet β cell reactive effector T cells and a deficiency of β cell-specific natural regulatory T cells (nTreg) in the peripheral T-lymphocyte repertoire. Insulin-like growth factor 2 (IGF-2) is the dominant member of the insulin family expressed during fetal life by the thymic epithelium under the control of the autoimmune regulator (AIRE) gene/protein. Based on the close homology and cross-tolerance between insulin, the primary T1D autoantigen, and IGF-2, the dominant self-antigen of the insulin family, a novel type of vaccination, so-called “negative/tolerogenic self-vaccination”, is currently developed for prevention and cure of T1D. If this approach were found to be effective for reprogramming immunological tolerance in T1D, it could pave the way for the design of negative self-vaccines against autoimmune endocrine diseases, as well as other organ-specific autoimmune diseases.